Food and Host Searching Decisions Made by Ibalia leucospoides (Hymenoptera: Ibaliidae), a Parasitoid of Sirex noctilio (Hymenoptera:Siricidae) - Pietrantuono, Ana Laura (2012)
During their adult life, parasitoids—insects that lay eggs in or on other arthropods eventually killing them- spend a significant proportion of their lifetime searching for hosts, this behavior will determine their future success, simply because fitness is closely related to host encounter (Godfray 1994). However, adult parasitoids are free living animals that in most cases need to acquire food for metabolic functions such as maintenance, survival and locomotion, as well as for reproduction. Feeding on sugar-rich products or else on host fluids (i.e. host-feeding) may imply benefits in terms of future fitness, by for instance increasing egg laying opportunities through increased egg production or longevity (Chapman 1998; Speight et al. 1999). In a biological control context, providing sugar sources in the field could in some conditions, increase the efficacy of parasitoids used as natural enemies of pests (Heimpel and Jervis 2005).